Retour d’expérience d’une première évaluation du Plan Réussite en Licence à l’Université de Bourgogne : les leçons d’un difficile recueil des points de vue enseignants et étudiants - Cathy Perret (Revue Internationale de Pédagogie de l’Enseignement Supérieur)
This article presents the results of an administrative enquiry on a French national programme for improving undergraduate students’ achievement rates that led to introducing new support activities in French universities as from 2007.  The paper analyses what the teachers and students involved in these programmes thought and believed about the programme and the support activities. The Centre for innovative teaching and evaluation led the study of experiences carried out at the University of Burgundy. The study shows the importance of teachers’ perceptions at the expense of students’ opinions. It highlights the limits of an administrative follow-up organised for monitoring purposes leading to issues in partiality and validity of the data available in the administrative files. It also emphasises the difficulties in drafting general conclusions on the programme and the various experiences carried out within the institution because of the wide range of positive and negative points according to the support activities and the courses. Nevertheless the study does indicate that the successes of certain student support activities are not measured out by student achievement rates - although this is the main goal of the national programme - but rather from the organisational side and from the teachers’ point of view. As a result the new tasks related to the student support activities are gradually assimilated by the teachers. The latter highlight the difficulties they face and question how they can manage the low attendance rates of support activities.